Faculty and Instructor Perceptions of Open Educational Resources in Engineering. Issue 4 (2nd October 2017) - Anderson, Talea; Gaines, Annie; Leachman, Chelsea; Williamson, Evan Peter
ABSTRACT: As open education initiatives aiming to lower the cost of course materials appeared at two universities, librarians became involved in identifying open educational resources (OERs) for university courses. However, when considering a number of subject areas—particularly in colleges focused on upper-division instruction—librarians encountered problems related to the availability of resources and materials selection processes. For this project, librarians selected one prominent subject area at their respective institutions—engineering—and worked to identify best practices for introducing OERs into courses. They surveyed engineering faculty and instructors to better understand their perceptions and needs related to OERs and, based on this work, they suggest best practices for liaison librarians in specialized fields who wish to incorporate OERs into their outreach work with a focus on upper-division courses.